Preliminary investigation of Ciprofloxacin-loaded microparticles for the treatment of bone diseases using coconut oil and shea butter - Olufunke Dorothy Akin-Ajani; Tomisin Awe; Kehinde Ademola Adediran (German Journal of Pharmaceuticals and Biomaterials, 2023)
Conventional drug delivery systems have several limitations, including poor bioavailability and an inability to effectively transport antibiotics to the needed site of infection in the bone. A formulation of ciprofloxacin-loaded microparticles derived from coconut oil and shea butter was developed to enable a selective and targeted distribution of the broad-spectrum antibiotic. Solid microparticles (SM), a mixture of solid and liquid lipid (coconut oil), solid-liquid microparticles (SLM), or coconut oil alone; liquid microparticles (LM), loaded with ciprofloxacin using the hot homogenization technique, were formulated. Evaluation of the microparticulate formulations included testing for particle size, the efficacy of entrapment, antibacterial activity, and in vitro drug release. The size of the microparticles that were loaded with ciprofloxacin ranked SM (5.25 ± 2.50 - 5.56 ± 2.01 μm) < SLM (7.94 ± 3.89 - 7.98 ± 2.00 μm) < LM (15.5 ± 1.50 - 20.29 ± 10.75 μm). The microparticulate formulations had an entrapment efficiency of 43.26% and 63.34% for the antibiotic ciprofloxacin. When tested against Staphylococcus aureus, all formulations exhibited good antibacterial activity; however, the microparticles generated from coconut oil and shea butter exhibited more significant antibacterial activity (zone of inhibition 24.0 ± 0.8 - 39.5 ± 9.2 mm), in comparison to the other formulations. LM had the fastest ciprofloxacin release (t50 = 5.5 min), but the microparticles formed from shea butter had a higher cumulative release (t50 = 12.7 min) compared to that from the mixture (p>0.05). These findings were obtained from in vitro drug release studies. The Korsmeyer-Peppas model could account for every formulation using the Fickian Case I transport mechanism. Because of their increased antibacterial activity, size, ability to entrap drugs, and in vitro drug release, the ciprofloxacin-loaded microparticles made from cold-pressed coconut oil combined with shea butter have the potential to provide a more effective treatment for bone diseases.